Effect of body mass index on functional outcomes following arthroplasty procedures - Polat, Gökhan; Ceylan, Hasan Hüseyin; Sayar, Şafak; Küçükdurmaz, Fatih; Erdil, Mehmet; Tuncay, İbrahim (Baishideng Publishing Group, 2015)
AIM: To evaluate the body mass index (BMI) change in arthroplasty patients and its impact on the patients' functional results. METHODS: Between October 2010 and May 2013, 606 patients who were operated due to gonarthrosis, coxarthrosis, aseptic loosening of the total knee and hip prosthesis were evaluated prospectively. Patients were operated by three surgeons in three medical centers. Patients who were between 30-90 years of age and who were underwent total knee arthroplasty, total hip arthroplasty, revision knee arthroplasty, or revision hip arthroplasty were included in the study. We excluded the patients who cannot tolerate our standard postoperative rehabilitation program. Additionally, patients who had systemic inflammatory diseases, diabetes mellitus, or endochrinopathies were excluded from the study. The remaining 513 patients comprised our study group. Preoperative functional joint scores, height, weight and BMI of all patients were recorded. We used the Knee Society Score (KSS) for knee and Harris Hip Score (HHS) for hip patients. Postoperative functional scores were measured at 1st, 6th and 12th months and recorded separately at outpatient visits. RESULTS: The mean age of the patients was 64.7 (range: 30-90) years (207 males/306 females) and the mean follow-up duration was 14.3 (range: 12-26) mo. We found that arthroplasty patients had weight gain and had an increase in BMI at the postoperative 1st, 6th and 12th months. The mean BMI of the patients was 27.7 preoperatively, 27.8 at the postoperative 1st month, 28.1 at the 6th month and 28.6 at the 12th month (P < 0.01). At the last visit, the mean postoperative HHS of the hip arthroplasty patients was 82.2 +/- 7.12 (preoperatively, 52.3; 1st month, 78.2; 6th month, 81.1; 12th month, 82.2), and the mean KSS of the knee arthroplasty patients was 79.3 +/- 4.31 (preoperatively, 35.8; 1st month, 75.2; 6th month, 79.1; 12th month, 79.3). Worse functional results were noted in the patients who had a BMI increase, however, this correlation was statistically significant only at the postoperative 6th month (P = 0.03). CONCLUSION: To prevent the negative functional effects of this weight gain during the postoperative period, arthroplasty patients should be advised for weight control and risky patients should consult with a dietician.
WOS: 000439318200016
PubMed ID: 26716096
Keywords: Body Mass Index; Arthroplasty; Obesity; Functional Outcomes; Weight Gain